An investigation into shrinkage and collapse behaviour of Eucalyptus grandis and Eucalyptus grandis x urophylla wood - Gonya, Nkosinamandla Artwel Sizwe (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScFor)--Stellenbosch University, 2020.